A child of two mothers: what about the father? Italian overview - Montanari Vergallo, Gianluca (Acta Biomedica Atenei Parmensis, 2019)
Surrogacy techniques allow for the birth of children who are then raised by parents who may have no genetic or biological connection with them at all. Italian legislation on medically assisted procreation bans such practices, under national criminal codes, and yet the intended parents’ ability to legally register children born abroad via surrogacy has not been affected by such legislation. Italian jurisprudence has acknowledged the parental status of same-sex couples, following the same path outlined by the European Court of Human Rights. The paper’s author elaborates on court decision n. 145/2018, from the Naples Court of Appeals, which has stated that surrogacy children may be connected to their intended parents merely by virtue of “mental” elements, based on affection, harmony and listening enjoyed by the child within the family setting. The author is critical of that view, in light of conflicting research findings on children growing up in same-sex families. In that regard, the author argues that even though homosexual couples may well turn out to be good parents, families made up of fathers and mothers still constitute the best scenario for the children, from a social perspective. It is however necessary for lawmakers to step in and better regulate an utterly sensitive area of law, one that might engender adverse repercussions on the children’s well-being, in terms of growth and psychological development, following their becoming part of homosexual families.